Inflammation and Cancer: Triggers, Mechanisms, and Consequences - Greten, Florian R.; Grivennikov, Sergei I. (Immunity (Cambridge, Mass.), 2019)
Inflammation predisposes to the development of cancer and promotes all stages of tumorigenesis. Cancer cells, as well as surrounding stromal and inflammatory cells, engage in well-orchestrated reciprocal interactions to form an inflammatory tumor microenvironment (TME). Cells within the TME are highly plastic, continuously changing their phenotypic and functional characteristics. Here, we review the origins of inflammation in tumors, and the mechanisms whereby inflammation drives tumor initiation, growth, progression, and metastasis. We discuss how tumor-promoting inflammation closely resembles inflammatory processes typically found during development, immunity, maintenance of tissue homeostasis, or tissue repair and illuminate the distinctions between tissue-protective and pro-tumorigenic inflammation, including spatiotemporal considerations. Defining the cornerstone rules of engagement governing molecular and cellular mechanisms of tumor-promoting inflammation will be essential for further development of anti-cancer therapies. Inflammation predisposes to the development of cancer and promotes all stages of tumorigenesis. Cancer cells, as well as surrounding stromal and inflammatory cells, engage in well-orchestrated reciprocal interactions to form an inflammatory tumor microenvironment (TME). Cells within the TME are highly plastic, continuously changing their phenotypic and functional characteristics. Here, we review the origins of inflammation in tumors, and the mechanisms whereby inflammation drives tumor initiation, growth, progression, and metastasis. We discuss how tumor-promoting inflammation closely resembles inflammatory processes typically found during development, immunity, maintenance of tissue homeostasis, or tissue repair and illuminate the distinctions between tissue-protective and pro-tumorigenic inflammation, including spatiotemporal considerations. Defining the cornerstone rules of engagement governing molecular and cellular mechanisms of tumor-promoting inflammation will be essential for further development of anti-cancer therapies.